Lipin-1 contributes to modified low-density lipoprotein-elicited macrophage pro-inflammatory responses. Issue 2 (October 2015) - Navratil, Aaron R.; Vozenilek, Aimee E.; Cardelli, James A.; Green, Jonette M.; Thomas, Michael J.; Sorci-Thomas, Mary G.; Orr, A. Wayne; Woolard, Matthew D.
Abstract: Atherosclerosis is a chronic inflammatory disease of large and medium-sized arteries and the underlying cause of cardiovascular disease, a major cause of mortality worldwide. The over-accumulation of modified cholesterol-containing low-density lipoproteins (e.g. oxLDL) in the artery wall and the subsequent recruitment and activation of macrophages contributes to the development of atherosclerosis. The excessive uptake of modified-LDL by macrophages leads to a lipid-laden "foamy" phenotype and pro-inflammatory cytokine production. Modified-LDLs promote foam cell formation in part by stimulating de novo lipid biosynthesis. However, it is unknown if lipid biosynthesis directly regulates foam cell pro-inflammatory mediator production. Lipin-1, a phosphatidate phosphohydrolase required for the generation of diacylglycerol during glycerolipid synthesis has recently been demonstrated to contribute to bacterial-induced pro-inflammatory responses by macrophages. In this study we present evidence demonstrating the presence of lipin-1 within macrophages in human atherosclerotic plaques. Additionally, reducing lipin-1 levels in macrophages significantly inhibits both modified-LDL-induced foam cell formation in vitro, as observed by smaller/fewer intracellular lipid inclusions, and ablates modified-LDL-elicited production of the pro-atherogenic mediators tumor necrosis factor-α, interleukin-6, and prostaglandin E2. These findings demonstrate a critical role for lipin-1 in the regulation of macrophage inflammatory responses to modified-LDL. These data begin to link the processes of foam cell formation and pro-inflammatory cytokine production within macrophages. Highlights: The phosphatidate phosphohydrolase lipin-1 was detected in human atherosclerotic plaques. Lipin-1 was required for modified LDL-elicited foam cell formation and TNF-α, IL-6 and PGE2 production. The loss of lipin-1 did not inhibit modified LDL uptake or enhance apoptosis of macrophages. These data begin to link the process of foam cell formation and foam cell inflammatory responses.